SOSIALISASI DALAM MELESTARIKAN TRADISI MAKAN DALAM KELAMBU PADA SUKU BUGIS - Handayani, Rizki; Bahari, Yohanes; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is "Socialization in preserving the tradition of eating in mosquito nets on Ethnic Bugis in Dusun Garuda, Sungai Kakap Subdistrict". This study aims to determine (1) the process of socialization in preserving the Eating In Mosquito Nets Tradition in Dusun Garuda, Sungai Kakap Subdistrict, (2) The process of carrying out the Tradition of Eating in Mosquito Nets in Dusun Garuda, Sungai Kakap Subdistrict. The method used in this research is descriptive method with a qualitative approach. Data collection techniques used are observation, interview, and documentation studies. While data collection tools are observation guidelines, interview guidelines, and documentation. The reseach involved four families as the informants. The Result of this study indicate the process of socialization of preserving the Eating Tradition in mosquito nets carried out orally by older family members to the younger generation. By the way, that is the first to transfer values regarding the Tradition of Eating In Mosquito Nets to the younger generation. Second, carry out social control so that the younger generation continues to carry out the Tradition. Then, the process of implementing the tradition of Eating In Mosquito Nets is divided into three sections. Namely preparing the completeness requirements for tradition, the core procession, and the closing procession. Keywords:  Socialization, Tradition, Bugis, Eating In Mosquito Nets.